2020
DOI: 10.1186/s12939-020-01293-2
|View full text |Cite
|
Sign up to set email alerts
|

Using implementation science to mitigate worsening health inequities in the United States during the COVID-19 pandemic

Abstract: With the threat of coronavirus disease 2019 (Covid-19) enduring in the United States, effectively and equitably implementing testing, tracing, and self-isolation as key prevention and detection strategies remain critical to safely re-opening communities. As testing and tracing capacities increase, frameworks are needed to inform design and delivery to ensure their effective implementation and equitable distribution, and to strengthen community engagement in slowing and eventually stopping Covid-19 transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…15 Through disaggregation, covid-19 research has rapidly identified disparities in outcomes and identified the need to design QI to tackle underlying determinants as well as quality of care received. 12 Design better Prioritise tackling barriers identified through your stakeholders of groups least served by the health system. Reaching the most disadvantaged will take innovations in strategies and learning from other groups already showing progress in these areas.…”
Section: Measure and Use Data Bettermentioning
confidence: 99%
See 2 more Smart Citations
“…15 Through disaggregation, covid-19 research has rapidly identified disparities in outcomes and identified the need to design QI to tackle underlying determinants as well as quality of care received. 12 Design better Prioritise tackling barriers identified through your stakeholders of groups least served by the health system. Reaching the most disadvantaged will take innovations in strategies and learning from other groups already showing progress in these areas.…”
Section: Measure and Use Data Bettermentioning
confidence: 99%
“…Measurement should include implementation outcomes such as acceptability and adoption and data elements needed to understand the underlying factors associated with success or failure in reducing inequity as quality improves. Disciplines such as implementation sciences and disparities research offer tools and frameworks that can accelerate this work 1112…”
Section: How Can We Do Better?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the underrepresentation of vulnerable populations in the study, it would have missed the identifications of the impacts of in/equity, which emerged in the third team’s analysis. Impacts of inequity on vulnerable populations show up throughout the literature, such as in language (James and Thériault 2020 ), economics (Harper 2020 ), culture (Harper 2020 ), health (Jacobson et al 2020 ), and disability (James and Thériault 2020 ). Any of these can have an impact on digital access (Coyne et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen sources described the availability of testing sites as a process barrier for testing, both in general (10,25,27,32) and in specific communities (18,24,27,29,33). Transportation barriers and access to testing centres play a role in accessing COVID-19 testing sites.…”
Section: Availability Of Testing Sitesmentioning
confidence: 99%